Should green jobs be outsourced? - Peter Philips (The University of Utah, Department of Economics, 2013)
The proposed Sempra 1250 megawatt (MW) tieline connecting the California grid to envisioned new wind-farms in Mexico is not just about electricity. It is also about foregone opportunities, lost human capital investment, lost worklives, lost tax revenues, and diminished economic development prospects; and also, it is about which regulatory authority, California or Mexico, should oversee the environmental impacts of building green generation capacity for the California grid. Finally, it is about undoing some of the economic benefits and jobs stimulated by the first set of federally subsidized, utilityscale, solar projects fast-tracked by the Interior Department.
Keywords: Q4; Q42; O1; O18; 330; renewable energy; construction; Imperial Valley; California; local economic development; photovoltaic solar energy generation; worker training; apprenticeship; local economic development